House of Churros: A feasibility study churros restaurant at Katipunan Ave. - Gaddi, Danielle Dane S. Genese, Jobelle Angela T. Pontillas, Jhanzel L. Puso, Louise Sebastian G. Verba, Maria Flor B. Villarama, Mary Grace S. 4 0 16; 5
ABSTRACT: House of Churros is a restaurant that caters to a variety of consumers by offering authentic churros along with other snacks and drinks. It is located in UP Town Center, Quezon City, and serves students, professionals, and families who want tasty and high-quality snacks. The restaurant will have a well-organized kitchen and a cozy dining area to ensure quality service. The market analysis shows a growing demand for churros, with projections indicating an increase in sales throughout the year. The restaurant will operate as a limited liability partnership with six partners, each managing different aspects of the business. House of Churros will use social media and participate in local events for the brand to be more visible to potential consumers. Financially, the partners will invest five hundred eighty-two thousand to cover startup costs, expecting to break even in about forty-three months. Additionally, the business aims to support local farmers by sourcing ingredients locally, contributing positively to the economy and promoting Filipino products. Keywords: House of Churros, Snack, Authentic Churros, Restaurant
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2